The growing importance of Enterococcus and Streptococcus Agalactiae in uncomplicated urinary tract infections - Jermakow, Katarzyna; Pajączkowska, Magdalena; Krzyżanowska, Barbara; Nowicka, Joanna; Dworniczek, Ewa (Family Medicine & Primary Care Review, 2016)
Background . Urinary tract infections (UTIs) represent 10-20% of all community-acquired infections. Escherichia coli remains the most commonly isolated microorganism. Because of the dominance of these bacteria, routine laboratory tests are not recommended in making the first UTI diagnosis. However, careful monitoring of all etiological agents of ncomplicated UTIs should be an important strategy for empirical therapy. Objectives . A determination of the incidence of UTI bacterial etiological agents in outpatients. Material and methods. The results of urine cultures were analyzed. The samples were obtained in the period from 01.2011 to 03.2013 from outpatients of all age groups. Results . The rods of Escherichia coli were the most frequently identified microorganisms responsible for uncomplicated UTIs. They were isolated from 52% of infected patients. Every fourth case of UTI indicated the participation of Enterococcus spp. And Streptococcus agalactiae . The next 21% of infections were caused by Gram-negative bacteria other than E. coli . The role of coagulase-negative staphylococci was insignificant and equaled less than 2%. Conclusions . Despite the dominant role of E. coli in urinary tract infections, there has been a decrease in the frequency of its isolation. However, the natural resistance of Enterococcus spp. to antibiotics increases the number of urinary tract infections caused by these bacteria. Streptococcus agalactiae is a UTI cause with similar frequency in women of reproductive age and postmenopausal women. Monitoring of the incidence of uncomplicated infections facilitates empirical treatment and prevents UTI recurrence.